2012
DOI: 10.1111/j.1939-0025.2011.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Restraint and seclusion use in U.S. School settings: Recommendations from allied treatment disciplines.

Abstract: Restraint and seclusion (R&S) are high risk, emergency procedures that are used in response to perceived violent, dangerous situations. They have been employed for years in a variety of settings that serve children, such as psychiatric hospitals and residential treatment facilities, but are now being recognized as used in the public schools. The field of education has begun to examine these practices in response to national scrutiny and a Congressional investigation. The fields of mental health and child welfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 38 publications
0
14
0
3
Order By: Relevance
“…The responsibility to implement effective practices should not be placed on the shoulders of local educators alone. Rather, federal, state, district, and building decision makers must work to establish the professional capacity to make these schools more effective learning environments for all students (Freeman & Sugai, 2013;LeBel et al, 2012). The policies and procedures reported in this article offer an important reference point for the field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The responsibility to implement effective practices should not be placed on the shoulders of local educators alone. Rather, federal, state, district, and building decision makers must work to establish the professional capacity to make these schools more effective learning environments for all students (Freeman & Sugai, 2013;LeBel et al, 2012). The policies and procedures reported in this article offer an important reference point for the field.…”
Section: Resultsmentioning
confidence: 99%
“…There are several factors that may contribute to the likelihood that restraint and seclusion will be used in school settings, including (a) the inclusion of students with significant emotional and behavioral needs in general education settings, (b) the lack of specialized support for students in these settings, and (c) the limited training provided to teachers and school staff to address intensive behavior support needs (LeBel, Nunno, Mohr, & O'Halloran, 2012). While restraint and seclusion continue to be used in school settings, there is a paucity of data supporting the effectiveness of these procedures to improve behavior (Curie, 2005).…”
mentioning
confidence: 99%
“…Many consider the use of restraint and seclusion on students to be generally ineffective (LeBel, Nunno, Mohr, & O’Halloran, 2012; May, 2011; NDRN, 2010; Westling, Trader, Smith, & Marshall, 2010). The physical nature of restraint and seclusion may actually reinforce nonsocial aggression in students (May, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, researchers and practitioners have attempted to reduce restraint. For example, LeBel et al (2012) reported that restraint and seclusion are used on children, adolescents, and youth in residential and educational settings and that these practices are traumatizing and dangerous to both the children and staff involved in each incident. In a study by Borckardt et al (2011), a reduction of restraint and seclusion was achieved in an inpatient psychiatric hospital and Campbell et al (2008) found a slight increase in the use of restraint when restraint training was provided to professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Restraint and seclusion traditionally have been used to interrupt or contain harmful behavior or to decrease the frequency of behavior in the future (Jones and Timbers 2002;LeBel et al 2012;Luiselli 2009). Restraint, by definition, limits mobility of parts of the body through the use of a manual method, a physical or mechanical device, material, or equipment (Mohr et al 2010); and seclusion is defined as confinement when a patient is physically prevented from leaving a room where the person is alone without the presence of others (National Council for Behavioral Health 2006).…”
Section: Introductionmentioning
confidence: 99%